1999
DOI: 10.1097/00007435-199901000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Subsequent Sexually Transmitted Infections Among Adolescent Women With Genital Infection Due to Chlamydia trachomatis, Neisseria gonorrhoeae, or Trichomonas vaginalis

Abstract: Subsequent STI frequently follow an initial STI, but there is substantial variation in the causal organism. These data suggest the importance of comprehensive STI prevention programs for adolescents rather than organism-specific interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 28 publications
10
100
1
Order By: Relevance
“…Moreover, in our study we detected six cases of multiple infections using the same DNA (Table I). These findings are consistent with literature data (15,24,25).…”
Section: Identification Of Std Pathogen Agents Via Multiplex Pcrsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, in our study we detected six cases of multiple infections using the same DNA (Table I). These findings are consistent with literature data (15,24,25).…”
Section: Identification Of Std Pathogen Agents Via Multiplex Pcrsupporting
confidence: 94%
“…These multiple infections involved 11.54% of the patients, a fairly large proportion. The association of various pathogens that cause STDs is quite common due to biological factors, such as a common route of transmission, the partners' sexual behavior and the associated flora (25).…”
Section: Distribution Of Std Pathogens In the Study Groupmentioning
confidence: 99%
“…Persons who use substances participate in behaviors that place them and others at substantial risk for these infections (Bachmann et al, 2000;Battjes et al, 1995;Belongia et al, 1997;Booth et al, 1993;Broers et al, 1998;Chiasson et al, 1991;Fortenberry et al, 1999;Francis, 2003;Garfein et al, 1998;Lorvich et al, 2001;Plitt et al, 2005;Poulin et al, 1999;Thomas et al, 1995;Zylberberg & Pol, 1996). Substance abuse treatment or various services provided in the mix of services in substance abuse treatments have been demonstrated to be important tools in developing effective responses to reduce the transmission of these infections (Brown, Chu, Nemoto, Ajuluchukwu, & Primm, 1989;Cooper, 1989;Hartel & Schoenbaum, 1998;Hubbard, Marsden, Cavanaugh, Rachal, & Ginsburg, 1988;Lally et al, 2002Lally et al, , 2005Metzger, Navaline, & Woody, 1998;Sorensen & Copeland, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Infections due to human immunodeficiency virus (HIV; the causative agent of acquired immunodeficiency syndrome [AIDS]), hepatitis C virus (HCV), and sexually transmitted infections (STIs) are the most prominent. Among substance abusers, the rates for these infections are especially significant; published studies indicate that 30-40% of injection drug users are HIV-infected (Battjes, Pickens, & Brown, 1995;Booth, Watters, & Chitwood, 1993;Chiasson et al, 1991;Francis, 2003;Zylberberg & Pol, 1996), 60-95% are HCV-infected (Broers et al, 1998;Garfein et al, 1998;Lorvich, Kral, Seal, Gee, & Edlin, 2001; Thomas et al, 1995;Zylberberg & Pol, 1996), and 90% have had at least one type of STI (Bachmann et al, 2000;Belongia et al, 1997;Fortenberry et al, 1999;Plitt et al, 2005;Poulin, Alary, Bernier, Ringuet, Joly, & 1999).…”
Section: Introductionmentioning
confidence: 99%
“…If infected male partners in the African-American community are not made aware of the need for diagnosis and treatment, women will continue to get reinfected. Given that numerous studies have shown high reinfection rates of T. vaginalis up to a year following treatment in African-American populations, and metronidazole resistance was not thought to be responsible, failure to screen and treat partners is a significant issue contributing to the high prevalence of infection in this community (25,72).…”
Section: Prevalence Of T Vaginalis Among Men In the United Statesmentioning
confidence: 99%